Influence of root dentin treatment on the push-out bond strength of fibre-reinforced posts - Altair Soares MOURA; Rodrigo Dantas PEREIRA; Fuad Jacob Abi RACHED JUNIOR; Bruno Monguilhott CROZETA; Jardel Francisco MAZZI-CHAVES; Luis Eduardo SOUZA-FLAMINI; Antonio Miranda CRUZ FILHO (Sociedade Brasileira de Pesquisa Odontológica, 2017)
Abstract This study evaluates the influence of root dentin treatment with NaOCl alone and combined with EDTA, with and without ultrasound activation, on the push-out bond strength (BS) of fiber-reinforced posts in weakened roots, cemented with RelyX or Panavia. The root canals of 42 maxillary canines were instrumented with Reciproc and 2.5% NaOCl. In the coronal 12mm of all canals, experimental weakening of the roots was produced by reducing dentin thickness with 2.44mm diameter diamond burs. The roots were assigned to 3 groups (n = 14) according to root dentin treatment: 2.5% NaOCl; 2.5% NaOCl + 17% EDTA; and 2.5% NaOCl + 17% EDTA, with solutions agitated using passive ultrasonic irrigation. After cementation of the fiber-reinforced posts the roots were divided in thirds. The first slice of each third was used for the push-out BS test, the second slice for confocal laser scanning microscopy and dentin microhardness (Knoop) analysis. Data were analysed by a two-way ANOVA and Tukey test (a = 0.05). NaOCl + EDTA provided highest BS values than NaOCl (p < 0.0001). Specimens cemented with Panavia presented significantly higher BS than those with RelyX in the three root thirds (p < 0.0001). The highest BS values occurred in the cervical third (p < 0.001). Ultrasound-activated NaOCl + EDTA promoted the greatest reduction in dentin microhardness, followed by NaOCl/EDTA and NaOCl. Ultrasonic activation of NaOCl and EDTA reduced root dentin microhardness, but did not improve the push-out BS of resin-based cements. Panavia presented higher BS than RelyX. RelyX was not influenced by the root dentin treatment protocols.